Children and youth at risk: The social management of risk. A literature review - Donovan, Patrick; Oñate, Ximena; Bravo, Gonzalo; Rivera, María Teresa (Última Década, 2020)
This article observes the way in which great contemporary transformations (economic, political and cultural) have an impact in the daily life of family, childhood and youth. Toward the problematic area, the literature of social sciences around the concept of management of social risk is explored, more specifically in the scope of childhood and youth in a difficult situation. In fact, the theory of the risk has nowadays become a great preoccupation, perhaps exaggerated and politically interested. This documentary observation predominantly collects and resists of materials of the United Kingdom, Latin America and Chile. Part of an historical revision of the risk concept identifies a series of theoretical schemes to approach it, and soon it is centered in the debate of management of the risk in relation to childhood in a difficult situation. It is observed that there is still lack of a model for social intervention of risk. Nevertheless, a continuation between two great tendencies is identified: one that is centered in control and looks to avoid the risk, whereas the other emphasizes the participation and the empowerment, taking positive risks. Questions for future investigations in this scope are included.